2019
DOI: 10.1042/bsr20181952
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms inCLDN1are associated with age and differentiation of triple-negative breast cancer patients

Abstract: Purpose: Triple-negative breast cancer (TNBC) is a highly heterogeneous disease. It is very important to explore novel biomarkers to better clarify the characteristics of TNBC. It has been reported that polymorphisms in claudin 1 (CLDN1) are associated with risk of several cancers. But till now, there is no report about these polymorphisms and TNBC. Patients and methods: Between January 2004 and December 2013, 267 patients with stage I–III primary TNBC were included in our study. We investigated the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In esophageal squamous carcinoma, CLDN1 was revealed to promote tumor development and invasion via autophagy activation through the 5′AMP-activated protein kinase/STAT1/Unc-51 like autophagy activating kinase (ULK1) signaling pathway [ 48 ]. In addition, CLDN1 was also found to be associated with the malignancy of hepatocellular carcinoma [ 49 ], cervical cancer [ 50 ], breast cancer [ 51 ], and gastric cancer [ 52 ]. In lung cancer, CLDN1 expression was reported to promote the chemotherapeutic resistance of NSCLC through ULK1 phosphorylation, but methylation of the CLDN1 gene can enhance the efficacy of chemotherapy to inhibit the progress of LUAD [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In esophageal squamous carcinoma, CLDN1 was revealed to promote tumor development and invasion via autophagy activation through the 5′AMP-activated protein kinase/STAT1/Unc-51 like autophagy activating kinase (ULK1) signaling pathway [ 48 ]. In addition, CLDN1 was also found to be associated with the malignancy of hepatocellular carcinoma [ 49 ], cervical cancer [ 50 ], breast cancer [ 51 ], and gastric cancer [ 52 ]. In lung cancer, CLDN1 expression was reported to promote the chemotherapeutic resistance of NSCLC through ULK1 phosphorylation, but methylation of the CLDN1 gene can enhance the efficacy of chemotherapy to inhibit the progress of LUAD [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Youssefian et al ( 51 ) reported that a novel mutation in CLDN1 was identified in neonatal ichthyosis and was associated with sclerosing cholangitis, referred to as the NISCH syndrome, which may be used for molecular confirmation of the diagnosis in some of these patients. Furthermore, polymorphisms in the CLDN1 gene were associated with the age of patients and differentiation of triple-negative breast cancer (TNBC), but there was no association between polymorphisms in CLDN1 and survival of patients with TNBC ( 52 ). However, the function of CLDN1 may vary even in the same type of cancer, such as breast cancer ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, polymorphisms in the CLDN1 gene were associated with the age of patients and differentiation of triple-negative breast cancer (TNBC), but there was no association between polymorphisms in CLDN1 and survival of patients with TNBC ( 52 ). However, the function of CLDN1 may vary even in the same type of cancer, such as breast cancer ( 52 ). Loss of CLDN1 expression in patients with breast cancer was associated with tumor invasion and metastasis by Tokés et al ( 53 ), whereas CLDN1 contributed to migration of luminal-like MCF7 human breast cancer cells ( 54 ).…”
Section: Discussionmentioning
confidence: 99%